2008
DOI: 10.1590/s0100-39842008000500013
|View full text |Cite
|
Sign up to set email alerts
|

Ressonância magnética e tomografia computadorizada da articulação temporomandibular: além da disfunção

Abstract: Várias doenças devem ser consideradas no diagnóstico diferencial dos distúrbios que comprometem as articulações temporomandibulares. A disfunção interna é a principal entidade responsável pelos quadros dolorosos desta articulação. Entretanto, os achados clínicos podem ser bastante inespecíficos e diversas outras condições se manifestam com sinais e sintomas semelhantes e, não raramente, indistinguíveis. Neste trabalho demonstramos, por meio de imagens de tomografia computadorizada e ressonância magnética, vári… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…CT comprises a set of images obtained through a sophisticated and highly accurate technique, compared to plane radiographs. 2 Recently, cone-beam computed tomography (CBCT) technology has been used for dental diagnosis due to its specific use for the maxillofacial region. 3 , 21 Its main advantage is the observation of boney joint structures in the sagittal, coronal, and axial planes, 1 , 21 in addition to the possible image manipulation at different depths and three-dimensional reconstruction 14 , 21 through specific software.…”
Section: Temporomandibular Joint Imaging Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…CT comprises a set of images obtained through a sophisticated and highly accurate technique, compared to plane radiographs. 2 Recently, cone-beam computed tomography (CBCT) technology has been used for dental diagnosis due to its specific use for the maxillofacial region. 3 , 21 Its main advantage is the observation of boney joint structures in the sagittal, coronal, and axial planes, 1 , 21 in addition to the possible image manipulation at different depths and three-dimensional reconstruction 14 , 21 through specific software.…”
Section: Temporomandibular Joint Imaging Assessmentmentioning
confidence: 99%
“…1 It is the most frequently used joint of the human body and has simultaneous bilateral capacity to move the mandible. 2 , 3…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These two methods are often combined to study the TMJ disorders, and they are important tools in the differential diagnosis of diseases that affect this region. 8 A study that compared the results of the position of the mandibular condyle obtained by TR and linear tomography reported that the results were more precise with tomographic images. Indeed, it was questioned whether TR is an appropriate method for measuring the position of the mandibular condyle.…”
Section: 5005/jp-journals-10024-1940mentioning
confidence: 99%